AI’s Impact on Students’ Oral Presentation Skills: Indonesian Lecturers’ Pedagogical Responses - Primandhika, Restu Bias; Solihati, Nani; Zulaiha, Siti (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
This study investigates lecturers’ pedagogical responses to student challenges in processing information for oral presentation skills in the era of artificial intelligence. Employing a qualitative case study design with thematic analysis, the study involved eight lecturers and 62 students from three private universities in Cimahi, Indonesia. Data were collected through in-depth interviews and Focus Group Discussions (FGDs) and analysed using Braun and Clarke’s six-phase thematic framework. The findings reveal that 1) all lecturer participants (100%) reported an erosion of students’ oral communication skills, manifested in a gap between high-quality visual artifacts and weak verbal performance, deficits in spontaneous responses, and degradation of non-verbal communication, indicating the role of artificial intelligence as a cognitive crutch, 2) lecturers responded to these challenges by diversifying pedagogical strategies, particularly through explicit AI usage policies (100%), intensified oral validation via spontaneous question-and-answer sessions (87.5%), and process-oriented assessment (75%), and 3) student responses were ambivalent, with the majority (77.4%) perceiving the new assessment approaches as fairer and more transparent, while a minority (22.6%) expressed resistance related to performance anxiety. These findings suggest that the most effective response to AI-related challenges is not the prohibition of technology, but a pedagogical redesign that prioritizes process validation, human interaction, and assessment security to maintain rigorous academic standards in Indonesian higher education.